EVALUATION DE LA QUALITÉ DE CERTAINES FACTEURS PÉDAGOGIQUES ET DIDACTIQUES DANS LA FACULTÉ DES SCIENCES DE KENITRA (MAROC), SELON LES ÉTUDIANTS DE LA FILIÈRE « LICENCE» - El Azizi Ouarda; Fouad Ouad; Fadli Anas; Chaouch Abdelaziz (European Scientific Journal, ESJ, 2015)
Since 1956, year of the independence of Morocco, the quality of education has suffered from many problems. The education system has known reform after reform without achieving the desired results. Thus, in the hope of participating in the development of a solution for this problem "chronic", this sector needs a profound diagnosis, which determines its weak points that block, and the constraints that oppose to the improving of Moroccan education. In the present work we contributed with a diagnosis whose purpose and to assess the degree of satisfaction of the students of the Faculty of Sciences of Kenitra (Morocco) of some activities or educational variables. The results show that among the 22 variables studied, the degree of student satisfaction exceeds 55% for 6 variables, between 45% and 55% for 4 variables, of 40% to 45% for 7 variables, and superior to 40% for 17 variables. The satisfaction rate is therefore less than 40% for only 5 variables. The dissatisfaction of students affects four areas of study ie study program, product availability and Lab equipment, student evaluation means and the conditions of the realization of end of Project study.